2020
DOI: 10.13106/jafeb.2020.vol7.no10.981
|View full text |Cite
|
Sign up to set email alerts
|

Technology Acceptance Model of Financial Technology in Micro, Small, and Medium Enterprises (MSME) in Indonesia

Abstract: Seeing the existence of MSME needs that have still not been met although this sector is undeniably important in Indonesian economy, changes in community behaviour and the intensity of the use of technology in the community, financial technology (fintech) has a lot of potentials to become a part of the solution of the problem commonly faced by MSMEs. Therefore this research needs to be done to observe the potential of fintech in integrating MSMEs in terms of the application of technology and knowledge from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 10 publications
1
23
0
2
Order By: Relevance
“…3 Extended Model of TAM (TAM2) [22] TAM was used between 1986-2003 to analyse user acceptance in different types of technologies ranging from communication, general-purpose, office and specialised business systems [23]. Recent studies also showed its application in studying building information modelling [26], digital payment systems [5], [27] , financial technology [4] and knowledge management [8]. According to [9], TAM has a robust implication on technology adoption from both theoretical and conceptual perspectives.…”
Section: B Technology Acceptance Model (Tam)mentioning
confidence: 99%
See 4 more Smart Citations
“…3 Extended Model of TAM (TAM2) [22] TAM was used between 1986-2003 to analyse user acceptance in different types of technologies ranging from communication, general-purpose, office and specialised business systems [23]. Recent studies also showed its application in studying building information modelling [26], digital payment systems [5], [27] , financial technology [4] and knowledge management [8]. According to [9], TAM has a robust implication on technology adoption from both theoretical and conceptual perspectives.…”
Section: B Technology Acceptance Model (Tam)mentioning
confidence: 99%
“…Moreover, [30] explained PU as the degree to which users believe that the use of technology will boost their performance. This means it is possible to measure perceived usefulness based on the technology's ability to improve firm performance, productivity, effectiveness, which will benefit businesses [4].…”
Section: Variables Of Tam 1 Perceived Usefulness (Pu)mentioning
confidence: 99%
See 3 more Smart Citations